2021
DOI: 10.1016/j.esxm.2021.100424
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Satisfaction and Associated Biopsychosocial Factors in Stroke Patients Admitted to Specialized Cognitive Rehabilitation

Abstract: Introduction: The consequences of stroke on sexual life in stroke patients in need of specialized cognitive rehabilitation have been limited explored. A biopsychosocial perspective in post-stroke sexuality studies is warranted to capture the complex picture of stroke consequences and sexual life after stroke and sexual satisfaction is an important outcome measure when exploring such multifactorial associations. Aim: To explore sexual satisfaction and associated biopsychosocial factors in stroke patients admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Preliminary psychosocial studies reported that unwillingness for sex, general attitude toward sexuality, inability to discuss sexuality, and a belief in an adverse effect of stroke were explanatory factors for decreased sexual satisfaction [ 11 , 38 ]. In a recent study, using a multivariate biopsychosocial approach, Vikan and colleagues [ 39 ] demonstrated that partner rejection and a decrease in sexual activity had a significant contribution to sexual dissatisfaction in stroke patients. In the realm of socio-demographic research, other factors should be taken into account when evaluating sexuality in stroke patients.…”
Section: A Biopsychosocial Perspective: Toward a Standardized Evaluat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary psychosocial studies reported that unwillingness for sex, general attitude toward sexuality, inability to discuss sexuality, and a belief in an adverse effect of stroke were explanatory factors for decreased sexual satisfaction [ 11 , 38 ]. In a recent study, using a multivariate biopsychosocial approach, Vikan and colleagues [ 39 ] demonstrated that partner rejection and a decrease in sexual activity had a significant contribution to sexual dissatisfaction in stroke patients. In the realm of socio-demographic research, other factors should be taken into account when evaluating sexuality in stroke patients.…”
Section: A Biopsychosocial Perspective: Toward a Standardized Evaluat...mentioning
confidence: 99%
“…Social resources also affect sexuality in stroke patients. Indeed, Vikan and colleagues [ 39 ] reported that affectionate support was the only factor that contributed to sexual satisfaction, demonstrating that having someone show you love and affection is crucial for total sexual fulfillment.…”
Section: A Biopsychosocial Perspective: Toward a Standardized Evaluat...mentioning
confidence: 99%
“…The researchers [7] emphasize, however, that even though sexual dysfunctions among the participants could occur due to brain injury location, dysfunctions could also occur due to psychosocial aspects, such as changes in relationships related to TBI. In a recently published Norwegian study, Vikan et al [22] investigated how several biopsychosocial factors were associated with lowered satisfaction with sexual life after stroke, and reported that two thirds were unsatisfied with their sexual life and that more females than males were experiencing sexual difficulties.…”
Section: Biopsychosocial Perspectivesmentioning
confidence: 99%